Access and comprehensiveness in health care for quilombola women: challenges to equity and guaranteeing the right to health (Research, Society and Development, 2022)
This theoretical essay aims to reflect on inequalities in access to health and the production of comprehensive care for quilombola women, focusing on equity, integrality and guaranteeing the right to health. The policies of Equity Promotion in Health and, more specifically, the National Policy of Integral Health of the Black Population (PNSIPN) were adopted as a reference. Two reflective axes were organized, namely: "Access to health care and racism: challenges to equity in health and ensuring the right to health" and "Integrality in health care for quilombola women: policies and care practices in primary care".  Inequalities of access to health services are identified, demarcated by economic and social vulnerabilities, in addition to practices of discrimination mainly racial, which negatively impact the living conditions of the black population. Despite the advances in the social and economic context, it is necessary to strengthen the instances of dialogue to resolve the obstacles evidenced in public policies that meet the demands of this population. In addition, it is perceived the need to confront racism, discrimination, vulnerabilities and injustices that hinder the promotion of integral health care for quilombola women in primary health care.